2009
DOI: 10.1029/2008gl036477
|View full text |Cite
|
Sign up to set email alerts
|

Low‐frequency seismic signals recorded by OBS at Stromboli volcano (Southern Tyrrhenian Sea)

Abstract: [1] Five three-component broadband ocean bottom seismometers (OBSs) were deployed on the seafloor around the Aeolian Islands (Southern Tyrrhenian Sea). By comparing OBSs digital seismograms, we found a lowfrequency seismicity recorded only at OBS05, the nearest seafloor station to Stromboli volcano. This seismicity appears in the form of a continuous seismic signal (tremor-like-signal) as well as a considerable number of shock-like events. We focused on recordings from OBS05 to verify their correlation with St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…We therefore notice the link between a monophase fluid (gas) and a single‐peak spectrum, while a double‐phase fluid (liquid‐gas) produces a two‐peak spectrum. Bimodal spectra have also been found at Stromboli volcano [ Sgroi et al ., ] and interpreted as the overlap of deep magmatic fluids and shallower fluids enriched of gas. This is consistent with our findings, confirming the key role played by the type and number of phases forming the fluid to the character of the fluid‐induced seismicity.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore notice the link between a monophase fluid (gas) and a single‐peak spectrum, while a double‐phase fluid (liquid‐gas) produces a two‐peak spectrum. Bimodal spectra have also been found at Stromboli volcano [ Sgroi et al ., ] and interpreted as the overlap of deep magmatic fluids and shallower fluids enriched of gas. This is consistent with our findings, confirming the key role played by the type and number of phases forming the fluid to the character of the fluid‐induced seismicity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the seismicity characterised by a frequency content between 4 and 10 Hz could be connected to hydrothermal fluids circulation, in analogy with long-period (LP) events (e.g., [58][59][60]), while those with 40-80 Hz frequency content could be generated by surface degassing phenomena ( [3] and references therein).The results of the chemical and isotopic analyses of gas extracted from the sampled sea-waters allow us to confirm the existence of a dissolved gas phase different from the atmospheric. The results clearly show that besides the expected atmospheric gases, a significant content of CO 2 marks all the gas samples.…”
Section: Discussionmentioning
confidence: 99%
“…Sgroi et al [57] identified the source of the LP events (recorded by OBS05) with the magmatic reservoir at 3 km, and the source of the explosion-quakes (recorded by land station) with the 400-m reservoir. Features of seismic signals recorded by the land station and OBS05 confirm the presence of two different seismic sources (Figures 3 and 4).…”
Section: Strombolimentioning
confidence: 99%
“…The mass removal process from the deeper part of volcanic conduits to its top is the dynamic component of an eruption. It is natural to infer that the OBS05 may be more sensitive to detecting the deeper components in the eruption process, while the land station will be more sensitive to the eruption dynamics near the surface [57]. …”
Section: Strombolimentioning
confidence: 99%
See 1 more Smart Citation